A Young man with Delirium Tremens, Pellagra and Alcoholic neuropathy. Case report and review of pharmacological treatment - B. Díez Valle; P. Coucheiro Limeres (European Psychiatry, 2022)
Introduction We present the case of a 36-year-old male with chronic alcoholism who suffered Delirium Tremens and other complications during hospital admission and who recovered thanks to treatment with benzodiazepines and antiepileptics using a cross tapering strategy.